Cardiac Autonomic Neuropathy in Diabetes: A Predictor of Cardiometabolic Events - Vinik, Aaron I.; Casellini, Carolina; Parson, Henri K.; Colberg, Sheri R.; Nevoret, Marie-Laure (Frontiers in Neuroscience, 2018)
Autonomic nervous system (ANS) imbalance manifesting as cardiac autonomic neuropathy (CAN) in the diabetic population is an important predictor of cardiovascular events. Symptoms and signs of ANS dysfunction, such as resting heart rate (HR) elevations, diminished blood pressure (BP) responses to standing, and altered time and frequency measures of heart rate variability (HRV) in response to deep breathing, standing, and Valsalva maneuver, should be elicited from all patients with diabetes and prediabetes. With the recognition of the presence of ANS imbalance or for its prevention, a rigorous regime should be implemented with lifestyle modification, physical activity, and cautious use of medications that lower blood glucose. Rather than intensifying diabetes control, a regimen tailored to the individual risk of autonomic imbalance should be implemented. New agents that may improve autonomic function, such as SGLT2 inhibitors, should be considered and the use of incretins monitored. Central to the mechanism of dysfunction is disturbance of the hypothalamic cardiac clock, a consequence of dopamine deficiency that leads to sympathetic dominance, insulin resistance, and features of the metabolic syndrome. An improvement in autonomic nervous system balance may be critical to reducing cardiovascular events, cardiac failure, and early mortality in the diabetic population.